Factors Associated With Hypertension Patients Compliance In Undergoing Treatment (Case Study at Alak Health Center, Kupang City in 2021) - Ase, Maria Veronika Yulianti Go’o; Sirait, Rina Waty; Dodo, Dominirsep O. (Timorese Journal of Public Health, 2023)
Hypertension is one of the most common cardiovascular diseases. One of the keys to successful treatment of hypertension is medication adherence. The problem is the lack of public understanding of the dangers of hypertension, which will check themselves to the health center only when they start to feel pain or symptoms of hypertension. This study aims to determine the factors associated with compliance with hypertension patients in undergoing treatment at the Alak health center in 2021. This type of research is an analytic survey, with a cross sectional research design. The sample size was 92 people with hypertension who were randomly selected with a compliance level of α = 0.05. Each variable studied was tested using the Chi-square test to determine the relationship with the variable level of compliance of hypertensive patients in undergoing treatment. Further testing using the coefficient of contingency test to determine the relationship between variables that show the existence of the relationship. The results showed that there was a relationship between the level of knowledge (p=0.014) history of hypertension treatment (p=0.029) and treatment motivation (p=0.000), while there was no significant influence between income, family history of hypertension, and affordability of access to health services (p>0.05). It is hoped that the community, especially family members of hypertensive patients, will play an active role in providing motivation and support so that they always take regular medication and are always obedient in carrying out treatment to health services. This is because the family plays an important role for people with hypertension in undergoing treatment.